On the impact of computer vision algorithms on sport training automation: proof of concept for shadow boxing virtual instructor - Makarov, I.; Petrov, S. (2021)
We overview several XR applications of deep convolutional neural networks to the opportunity for creating an automated sports training process. From smart soccer and basketballs to automated fitness training programs, the progress of computer vision methods combined with personalized recommender systems and specific data science algorithms allows one to train non-contact training processes in a semi-automated manner with virtual mirrors and XR devices. We overview modern progress in this area and also present our own prototype of Shadow Boxing simulator for Virtual Mirror aiming to match part of boxer training with automated control and gamification process. We show that the trend of automating training instructors in sport leads to a positive shift in sportsmen and trainees` view of artificial intelligence in common life.